2021
DOI: 10.3389/fmed.2021.661032
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Rare Pulmonary Sclerosing Pneumocytoma: Large, Multiple, Metastatic, and Fatal

Abstract: Pulmonary sclerosing pneumocytoma (PSP) is a rare benign or low-grade malignant tumor, but it has the potential to present with multiple lesions, lymph node metastasis, extra-pulmonary metastasis, recurrence and even cause death. Herein, a case of PSP that was huge, presented with multiple lesions and had lymph node as well as extrapulmonary metastases (liver, abdominal cavity, bones) is reported for the first time. This patient was also the first one to die of respiratory and circulatory failure caused by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…He suggested that BRAF V600E mutation and AKT1-E17K pathway activation may be related to PSP carcinogenesis. Zhang et al 8 and Fan et al 53 through somatic mutation sequencing and pathway analysis also showed that the activation of AKT1 may be involved in the occurrence and development of PSP. Many researchers have discovered the activation of the AKT1-p.E17K pathway in their patients and believe that this activation may be related to the occurrence and metastasis of PSP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…He suggested that BRAF V600E mutation and AKT1-E17K pathway activation may be related to PSP carcinogenesis. Zhang et al 8 and Fan et al 53 through somatic mutation sequencing and pathway analysis also showed that the activation of AKT1 may be involved in the occurrence and development of PSP. Many researchers have discovered the activation of the AKT1-p.E17K pathway in their patients and believe that this activation may be related to the occurrence and metastasis of PSP.…”
Section: Resultsmentioning
confidence: 99%
“…Six of the 8 PSP with growth patients were observed only, and the increase was found after 6–492 months (median [IQR]: 42 months (34.75–120)), and then surgical resection was performed again. One of the patients died after gradual enlargement of the tumor during observation, 8 and one patient who was not followed up in a timely manner underwent pneumonectomy because the tumor size increased. 46 Some patients even had extrapulmonary metastases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical resection is usually recommended for the treatment of PSP [6] considering that cases with lymph node metastasis [3,[8][9][10][11][12][13][14], distant or pleural metastasis [15][16][17], recurrence [18], malignant transformation [19] and death [20] have been reported. However, as most patients with PSP show a benign indolent course, not all patients with PSP undergo surgical resection clinically [21].…”
Section: Introductionmentioning
confidence: 99%